Propagation of Tectaria coadunata (Wall. ex Hook. & Grev.) C.Chr by Spores - Thakur, Chandrakala; Parajuli, Raghu Ram; Budhathoki, Prativa; Rajbhandary, Sangeeta (Journal of Plant Resources, 2022)
This study explores the spore germination and formation of sporophyte of Tectaria coadunata (Wall. ex Hook. & Grev.) C.Chr from its spores. Tectaria coadunata is a perennial evergreen edible fern species belonging to the family Tectariaceae. It is locally known as kali niuro in Nepali language and it is a very common wild vegetable in Nepal. We carried out the successful propagation of Tectaria coadunata from spores using two propagating media: coco-peat and soil mixture (soil, sand and compost manure).The temperature recorded from the spore sown time to development of sporophyte phase was 18-27°C while the general florescent light regime for 14-16 per day was supplied. To keep the propagating media humid and moist it was regularly monitored and maintained. The research is now in acclimatize phase and success of this study will be shared soon. Moreover, the work is successful in laboratory under control condition of certain factors like light and moisture and it is under progress to exploit its capacity to get survived in natural field, and the findings could be used as an alternative method of raising the plant in semi-natural environment.